2016
DOI: 10.4049/jimmunol.1502358
|View full text |Cite
|
Sign up to set email alerts
|

A MicroRNA-Mediated Positive Feedback Regulatory Loop of the NF-κB Pathway in Litopenaeus vannamei

Abstract: In the evolutionarily conserved canonical NF-κB pathway, degradation of the NF-κB inhibitor IκB in the cytoplasmic NF-κB/IκB complex allows the liberated NF-κB to translocate into the nucleus to activate various target genes. The regulatory mechanism governing this process needs further investigation. In this study, a novel microRNA, temporarily named miR-1959, was first identified from an invertebrate Litopenaeus vannamei. miR-1959 targets the 3′-untranslated region of the IκB homolog Cactus gene and reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…To further confirm the above results, we probed Dorsal translocation from the cytoplasm to the nucleus upon WSSV infection by using an L . vannamei Dorsal specific antibody prepared in our previous study [ 49 ]. In good agreement with the results of immunofluorescence staining, we were able to detect more nuclear import of Dorsal in shrimp hemocytes along with the times of WSSV infection from 0 h to 6 h, while at 6 hpi only a slight signal of Dorsal can be detected in the cytoplasm ( Fig 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the above results, we probed Dorsal translocation from the cytoplasm to the nucleus upon WSSV infection by using an L . vannamei Dorsal specific antibody prepared in our previous study [ 49 ]. In good agreement with the results of immunofluorescence staining, we were able to detect more nuclear import of Dorsal in shrimp hemocytes along with the times of WSSV infection from 0 h to 6 h, while at 6 hpi only a slight signal of Dorsal can be detected in the cytoplasm ( Fig 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been well known that miRNAs are involved in various biological processes in eukaryotes, including cellular proliferation, development, differentiation, metabolism, oncogenesis, and apoptosis [36]. They negatively regulate gene expression through binding to the 3′ untranslated regions (UTRs), 5’UTRs, or the coding regions of target mRNA [79]. Since the first discovery of the miRNAs lin-4 and let-7 in Caenorhabditis elegans in 1993 [10], numerous miRNAs have been identified in mammals, plants, insects, worms, and viruses [1114].…”
Section: Introductionmentioning
confidence: 99%
“…To gain more information on nuclear translocation of Dorsal upon WSSV infection, we firstly detected the dynamics of Dorsal translocation at several times, and we observed that shrimp hemocytes exhibited gradually and significantly increased nuclear translocation levels of Dorsal (53%, 88% and 94%) compared to the control hemocytes treated with PBS (Normal 0 h, 20%) at 1 h, 3 h and 6 h after WSSV challenge, respectively (Figures 5B and b). To further confirm the above results, we probed Dorsal translocation from the cytoplasm to the nucleus upon WSSV infection by using an L. vannamei Dorsal specific antibody prepared in our previous study (44). In good agreement with the results of immunofluorescence staining, we were able to detect more nuclear import of Dorsal in shrimp hemocytes along with the times of WSSV infection from 0 h to 6 h, and at 6 hpi almost no signal of Dorsal can be detected in the cytoplasm (Figure 5C).…”
Section: Resultsmentioning
confidence: 68%
“…The polyclonal antibodies for L. vannamei Dorsal and Cactus were produced in guinea pigs and rabbits, respectively, by GL Biochem antibody manufacturing company (China) from our previous study (44). Polyclonal rabbit anti-NF-κB p65 (phospho S276) antibody (ab194726, Abcam) was used to detect the phosphorylated shrimp Dorsal.…”
Section: Methodsmentioning
confidence: 99%